Home or supervised rehabilitation following anterior cruciate ligament reconstruction: a randomized controlled trial. - Beard, D; Dodd, C (1998)
Rehabilitation following anterior cruciate ligament (ACL) reconstruction is varied. Patients are usually prescribed an independent home exercise program, although some patients may attend physical therapy for additional supervised exercise. It is not known whether additional supervised exercise provides any further benefit. The purpose of this study was to compare efficacy for two types of rehabilitation following ACL reconstruction. A randomized controlled trial of 31 ACL-reconstructed patients was used to test the hypothesis that a home program plus supervised rehabilitation (Group S) is more effective than a home program (Group H) alone. Function, activity level, anterior tibial translation, and muscle strength were measured preoperatively and at 3 and 6 months postoperatively. Improvement of function, activity level, muscle strength, and anterior tibial translation was evident in both groups, but no significant differences were found between groups even though the sample size was sufficient to detect small treatment effects. It was concluded that supervised exercise, in addition to a home program, has minimal extra benefit for patients who have undergone ACL reconstruction.